Navigating the next Industrial revolution: Future Work Force analysis based on Western Australian narrative - Pasan Ganegama (Research Synergy Foundation, 2019)
The study adopts a Focus group discussion than the more dominant quantitative data in studying Western Australian Business landscape and it’s local and global disrupters, repellents and extractors are exhaustively and critically analyzed. In order to ascertain needed competencies to navigate the next industrial revolution, current practices of government and non-government initiatives can be Juxtaposed to rowing and rafting phenomena. The current global strategic HR perspective should be focused, fast and flexible but the Australian Government and most corporate conglomerates view are it should be Safe, Slow and Strict. People make sense of their world where human actions are based upon the person's interpretation of events, societal meanings, intentions and beliefs (Gill and Johnson 20101; Denzin and Lincoln, 20052). The Australian public’s belief in navigating the next industrial revolution and the effect of Government policy-making is analyzed critically in this paper. The following two questions being answered with practical disparity and in the end, adjusted accordingly to make sense to the layman terms. First “Why we need to reimagine Human Resource Management perspective?” was unveiled. Secondly, the key features of future Human Resource Management were questioned. Thirdly what should the Australian corporates and Governments do differently to assimilate our workforce to reap benefits from the next industrial revolution is discussed. Finally championing the change using the right blend of leadership style and scale of change discussed in length to add clarity to the perspective.